Discussion of Toward Experimental Criteria for Judging Disclosure Improvement - McDonald, Daniel L. (Journal of Accounting Research, 1969)
The specified objective of Stallman's paper is to develop a criterion for judging disclosure under experimental conditions. It does not purport to test real world phenomena. At least two of the assumptions need to be highlighted. One is that the objective of accounting is to report relevant financial information useful for decision making. There can be little quarrel with this. A second is implied rather than explicitly stated: that improved disclosure increases usefulness or, more specifically, that more information aids those who use the best analytic techniques while at the same time improves or leaves unaffected the decisions made by those using less adequate analytic techniques. Such a Pareto Optimality view suggests that if the experiment is repeated, some less sophisticated investors should be included to investigate the validity of this second assumption.